DEVELOPMENT OF PROFESSIONAL COMPETENCE OF FUTURE DEFECTOLOGISTS IS THE BASIS FOR TRAINING COMPETITIVE PERSONNEL - Khayitov Lazizbek Rustam ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The republic has created a regulatory framework for the training of competitive bachelor speech therapists, which is a factor in the successful socialization of persons with disabilities. The article highlights the scientific and theoretical foundations of the model of professional competence development of future speech therapists.